HARGA POKOK PRODUKSI UNTUK PENENTUAN HARGA JUAL KAIN TENUN SONGKET MELATI DESA BURAI, KABUPATEN OGAN ILIR - Mariskha Z; Rita Martini; Maria Agustin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
Prices play an important role in the sale and purchase agreement from producers to consumers. Through pricing, the product feasibility position will be seen from its economic value. The purpose of setting a price is to reach the company's target, get profit from sales, increase and develop product production, and expand marketing targets. Burai songket weaving craftsmen, especially the Melati songket weaving craftsmen group located in Burai Village, Tanjung Batu Subdistrict, Ogan Ilir Regency are housewives with a total of 5 members. The group of Melati songket weavers has financial problems, especially capital. Craftsmen have been receiving material from investors so that craftsmen do not know what the raw material price is, the cost of goods manufactured and the cost of goods sold. Therefore craftsmen cannot determine the selling price of the finished product. Fabrics that have been finished weaving will be sold or returned to the buyer or investor at a price determined by the buyer or investor. Craftsmen are only as wage-takers so they cannot increase income and welfare. The solutions and output targets that will be achieved are offered by the team that will help provide raw materials in the form of threads, calculate raw material prices, calculate the cost of production and the selling price of each songket motif or product. In addition, the team will help train partners to be able to perform financial calculations properly.